Is there a need to increase the dose of efavirenz during concomitant rifampicin-based antituberculosis therapy in sub-Saharan Africa? The HIV-TB pharmagene study. (July 2015) - Habtewold, Abiy; Makonnen, Eyasu; Amogne, Wondwossen; Yimer, Getnet; Aderaye, Getachew; Bertilsson, Leif; Burhenne, Jürgen; Aklillu, Eleni
Aims: The current HIV treatment guidelines are inconsistent about the need for weight-based efavirenz dose adjustment during rifampicin containing antituberculosis (anti-TB) cotreatment. We investigated effect of rifampicin-based anti-TB cotreatment on plasma efavirenz exposure and treatment outcome, considering effect of CYP2B 6 genotype and bodyweight.Patients & methods : HIV-only (arm 1, n = 285) or TB–HIV (arm 2, n = 208) coinfected patients were enrolled and received efavirenz-based ART alone or with rifampicin-based anti-TB therapy, respectively. Plasma efavirenz concentrations at 4th and 16th weeks, viral load and CD4 cell count at 24th and 48th weeks were determined.Results : The mean plasma efavirenz concentration at weeks 4 (p = 0.03) and 16 (p = 0.08) was inconsistently higher in arm 2 than arm 1, mainly in CYP2B6*6 carriers. Effect of bodyweight on efavirenz pharmacokinetics was significant only in arm 1, but not in arm 2. Proportion of patients with nondetectable viral load (≤50 copies/ml) at week 24 was higher in arm 1 than arm 2 patients (91.0 vs 76.3%; p = 0.002), but no significant difference was observed at week 48 (89.5 vs 87.8%; p = 0.22).Conclusion : Rifampicin-based anti-TB cotreatment has no significant influence on long-term efavirenz plasma exposure and efficacy. Hence, there is no need to increase the dose of efavirenz during concomitant rifampicin-based anti-TB cotreatment in the sub-Saharan African population.